Methods to reduce losses at power transmission lines and a sample application - (:unkn) unknown (My University, 2010)
Voltage drop and power and energy losses occur during the transmission of energy produced at power plants through transmission and distribution Networks and many transformer stations. While most of the losses happen due to the value of the current flowing through the network and parameters of the devices, there are losses that are independent of load current. If the reasons of these losses can be identified properly in the network, the ways to mitigate them can be easily identified. This study will explain reasons of losses in power transmission lines due to load current and derive equations concerning the losses. It will also identify precautions to take in order to reduce losses due to load current. It will mathematically be proved gains obtained from reduction of losses. It will also build a model for Tavşanli{dotless} switchyard using Matlab Power System Analysing Toolbox (PSAT)and analyse data obtained from implementation of methods used in our study and in literature on this new model. © 2010 Praise Worthy Prize S.r.l.
Keywords: Losses; Power system analysing; Reduction of losses at power transmission lines